Mediação de conflitos na ouvidoria da Universidade Federal de Santa Maria - Silva, Marcelo Tascheto da (2024)
Due to the increase of interpersonal disagreements among students, professors and staff at the Federal University of Santa Maria in which disagreements have become expensive and slow disciplinary administrative processes, this study tried to analyze conflict mediations carried out at the ombudsman's office from January 2022 to December 2023. The aim of this paper was to check the effectiveness of mediations, as well as to connected those mediations to disciplinary administrative processes that came from disagreements, for then in light of the results, to propose a standing committee for conflict mediations at UFSM. To achieve the purpose of this work it was made a documentary analysis on the website Fala.BR with the manifestations involving conflicts among students, professors and staff, as well as an analysis of mediation sessions. The results found in this paper showed that is achievable a committee for conflict mediations at UFSM because mediation can solving conflicts without dispute, strengthen the dialogue among people and avoid more administrative processes, mainly those are not so complicated. Thus this work will help managements to better understand genesis of conflicts and the importance of a pacifc resolution.